Deneys Reitz se deelname aan die Anglo-Boereoorlog - Calitz, Gerhard; Pretorius, Fransjohan (Faculty of Humanities, University of the Free State, 2011)
One of the most remarkable books on the Anglo-Boer War is Deneys Reitz’s Commando: A Boer journal of the Boer War (London, 1929). It is based on his memoirs written in 1903 in Dutch. This paper takes these two sources into consideration and tells the story of how Deneys Reitz joined the Pretoria Commando at the age of 17 and how he participated in all the phases of the war. It is not the story of an officer or a professional soldier, and it focuses on Reitz’s view of the war. It says very little of military strategy and tactics. The war is seen from his unique perspective. It provides reasons for the war, the way the Boers fought, their weaknesses, the horrors of battles, the Boers’ lack of discipline and the quality of some of their commanders. Reitz provides a description of the war that starts with the mobilisation of the Boer forces in September 1899, and continues with the siege of Ladysmith and all the battles that he participated in. It provides perspectives on what it was to be a guerrilla fighter, and on the shortage of ammunition, food, clothes, horses, etc. – in short, life on commando. The book is written in simple language, but it is extremely realistic and has become a classic in the literature of the Anglo-Boer War. The purpose of this article is therefore to provide a short overview of Reitz’s involvement in the Anglo-Boer War.
Keywords: Anglo-Boer War; Reitz, Deneys; Reitz’s view of the war; Life on commando; Boer war commando; Pretoria Commando